Hypertention with Left Atriumabnormalities, Left Ventricular Hypertrophy, Qt Interval and the Smoker (Indian Journal of Public Health Research & Development, 2020)
Context: Nicotine in cigarettes Stimulates the release of the hormone adrenaline thereby increasing bloodpressure. Hypertension or Increase. blood pressure increases the pressure in the left ventricular muscleroomates Appears as hypertrophy. then an increase is in left atrial pressure Followed by left atrial dilatationspace. Hypertensive people who smoke cause disruption of the process of ventricular de polarization andre polarization of the heart. This study aims to analyze hypertension with left atrial abnormalities, leftventricular hypertrophy, and QT interval in smokers at Tower Hanyar Health Center. The observational studydesign uses descriptive method with cross sectional design. The sample consisted of 60 research subjectsand was divided into two groups, namely the group of smokers with hypertension with a total of 30 peopleand the group of non-hypertensive smokers with the number of 30 people Obtained by consecutive samplingmethod. In the study found the relationship of hypertension with left atrial abnormalities, left ventricularhypertrophy and QT interval in smokers tested the hypothesis with Chi-square test with a confidence level of95%, with ap value = 0.00. The results of the analysis of PROVE that there is a relationship of hypertensionwith left atrial abnormalities, left ventricular hypertrophy and left the QT interval in smokers at TowerHanyar Health Center. left ventricular hypertrophy and QT interval in smokers tested the hypothesis withChi-square test with a confidence level of 95%, with ap value = 0.00. The results of the analysis of PROVEthat there is a relationship of hypertension with left atrial abnormalities, left ventricular hypertrophy and leftthe QT interval in smokers at Tower Hanyar Health Center. left ventricular hypertrophy and QT interval insmokers tested the hypothesis with Chi-square test with a confidence level of 95%, with ap value = 0.00. Theresults of the analysis of PROVE that there is a relationship of hypertension with left atrial abnormalities,left ventricular hypertrophy and left the QT interval in smokers at Tower Hanyar Health Center.
Keywords: Left atrial abnormality, Left ventricular hypertrophy, QT interval, smoking, hypertension